Labor Unions and Management’s Incentive to Signal a Negative Outlook* - Bova, Francesco (Contemporary Accounting Research, 2013)
Evidence suggests that the negotiated wage for a unionized employee group is an increasing function of the firm’s prior profitability. As a result, managers may have an incentive to strategically signal a negative outlook to their unionized workers in order to improve the firm’s bargaining position. I assess the strategy of missing mean consensus analysts’ earnings estimates as a way for managers to signal a negative outlook to their unionized employees. I find that unionized firms are more likely to miss estimates than their nonunionized counterparts. Additionally, this propensity to miss estimates is increasing in both the firm’s percentage of unionized employees and multiunionism, but is unaffected by the timing of the signal relative to contract renewal. Finally, the increased propensity to miss estimates appears to be driven by both differences in expectations management and earnings management across the two groups. Specifically, managers of unionized firms take less action than their nonunionized counterparts to guide forecasts downward when estimates are too high, and they take more action to deflate earnings when expectations are too low. Taken together, the findings suggest that managers do seek to project a negative outlook to their unions, and that this tendency is increasing in the union’s negotiation strength.